Eco-friendly synthesis of ZnO nanoparticles using Cannabis sativa and assessment of its activities as efficient dyes removal and antioxidant agent. Issue 16 (16th December 2022) - Shahzadi, Tayyaba; Rehman, Sidra; Riaz, Tauheeda; Zaib, Maria
ABSTRACT: In reported work, zinc oxide nanoparticles (ZnONPs) had been synthesised by a green method using aqueous extract of Cannabis sativa leaves. A facile, eco-friendly, time saving and beneficial procedure for the preparation of metal nanoparticles had been developed. UV-visible spectroscopy, Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDX) were used to characterise the ZnONPs composition, their shape, size and crystallinity. Ultraviolet-visible spectra showed the absorbance band between 300 and 400 nm, which indicated the synthesis of stable ZnO nanoparticles. Average size of ZnONPs was calculated from XRD as 46 nm. SEM and EDX spectra confirmed the synthesis of spherical shaped ZnONPs. FTIR spectra showed that different functional groups were present in aqueous extract of plant's leaves, which acted as reducing agents in the formation of stable ZnONPs. The value of DPPH radical inhibition percentage shown by ZnONPs was 88 ± 0.08% at 1500 µg/ml concentration revealing its good antioxidant activity. The total antioxidant activity calculated for ZnONPs was 0.521 ± 0.34 against BHT as standard. Total phenolic contents for ZnONPs was calculated to be 292.60 ± 1.12 mg/g GAE. Then the synthesised ZnONPs were utilised as catalyst for the removal of harmful organic dyes methylene blue (MB) and Congo red (CR). Various factors like adsorbent dosage, dye concentration, pH and temperature were studied and optimised for maximum removal of dyes. Pseudo-first-order model was followed for adsorption kinetics of both dyes. Adsorption isotherms were also assessed using Freundlich and Langmuir isotherm models. Hence, green approach was easy and cost effective for the removal of organic dyes and found as efficient antioxidant in current study.